Advanced optical simulation tools in the OASYS suite and their applications to the design of last generation synchrotron radiation beamlines. Issue 1 (1st December 2022) - Rebuffi, Luca; Shi, Xianbo; Sanchez del Rio, Manuel
Abstract: Since 2013, OASYS (OrAnge SYnchrotron Suite) has been developed as a versatile, user-friendly and open-source graphical environment for modeling X-ray sources, optical systems, and experiments. Its concept stems from the need for modern software tools to satisfy the demand for performing more complex analyses and designing optical systems for 4th generation synchrotron radiation and FEL facilities. The ultimate purpose of OASYS is to integrate in a synergetic way the most powerful calculation engines available to perform virtual experiments in a synchrotron beamline. For X-ray Optics, OASYS integrates different simulation strategies by implementing adequate simulation tools, which communicate by sending and receiving encapsulated data. The OASYS suite has been extensively used in the optical design process for the upgrade projects of several synchrotron radiation facilities worldwide. Several new tools have been created to perform advanced calculations needed for the design of the beamlines and provide accurate specifications for the procurement of the optics.